(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The article presents the data on the new species of Crimean bryophlora, collected in the plain part of the Crimea in 2003-2009. Such species as Acaulon triquetrum (Spurse) H. Müll., Bryum klinggraeffii Schimp., B. kunzei Hornsch., B. moravicum Podp, Dicranella heteromalla (Hedw.) Schimp., Entostodon hungaricus (Boros) Loeske, Microbryum curvicollum (Hedw.) Zander, Physcomitrium pyriforme (Hedw.) Brid., Protobryum bryoides (Dicks.) Jguerra & M.J. Cano, Pterygoneurum kozlovii Laz., Sciuro-hypnum oedipodium (Mitt.) Ignatov & Huttuman, S. starkei (Brid.) B.S.G. are found in the Crimean Peninsula for the first time.